Equity and the Technology Transfer Strategies of American Research Universities - Feldman, Maryann; Feller, Irwin; Bercovitz, Janet; Burton, Richard (Management Science, 2002)
American universities are experimenting with new mechanisms for promoting the commercialization of academic research and generating revenue from university intellectual property. This paper discusses mechanisms available to universities in managing the commercialization of intellectual property, considering equity as a technology transfer mechanism that offers advantages for both generating revenue and aligning the interests of universities, industry and faculty. Employing data from a national survey of Carnegie I and Carnegie II institutions, we document the recent rise in university equity holdings. We present and estimate a model that considers the university's use of equity to be a function of behavioral factors related to the university's prior experiences with licensing, success relative to other institutions, and the organization of the technology transfer office, as well as structural characteristics related to university type.